ANALISIS SYNTAXIC ANALYSIS OF THE FABLE TIMUN MAS BY DEDE FIRMANSYAH: A STUDY OF STRUCTURE, TYPES, FUNCTIONS AND MEANING OF PHRASE - Alfi Najua Nabila; Ayu Diana; Septivan Wismo Pratama; Thio Zaki Pamungkas; Endang Sholihatin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Fairy tales or folk tales are an important part of Indonesia's cultural heritage. These stories often relate to the origins of a place, character, animal, or object. The objectives of this research are (1) To know the structure of phrases in the fairy tale Timun Mas by Dede Firmansyah; (2) Know the types of phrases in the fairy tale Timun Mas by Dede Firmansyah; (3) Knowing the function of phrases in the fairy tale Timun Mas by Dede Firmansyah; (4) Know the meaning of the phrase in the fairy tale Timun Mas by Dede Firmansyah. The research method used is a qualitative descriptive method with a grammatical approach. Conclusion (1) The phrase structure in the fairy tale Timun Mas by Dede Firmansyah is explained as an arrangement of words or groups of words that form a syntactic unit that can be found in the description of the characters, setting and actions that occur in the story; (2) The types of phrases in the fairy tale Timun Mas by Dede Firmansyah are nominal phrases, verbal phrases, adjectival phrases, prepositional phrases and adverbial phrases; (3) The function of phrases in the fairy tale Timun Mas by Dede Firmansyah is to build character, convey action, set the tempo and atmosphere, explain the setting, connect events, convey a moral message; (4) The meaning of the phrases in the fairy tale Timun Mas by Dede Firmansyah are moral messages, cultural symbolism, character development, setting the atmosphere, life lessons.